Construction of Archimedean copulas using total time on test transforms - Nair, N. Unnikrishnan; Vineshkumar, B. (South African Statistical Journal, 2024)
In the present work, we propose a method of constructing Archimedean copulas using the total time on test transform, extensively used in reliability modelling. It is observed that the copula can be specified in terms of a univariate life distribution with a finite mean and monotone hazard rate. We discuss some new properties of the Kendall distribution arising from the proposed new generator and the associated measures of dependence.